Analysis of Student Reading Interests During Learning from Home in the COVID-19 Pandemic - Titi Setiyoningsih; Fikry Zahria Emeraldien; Yanuar Bagas Arwansyah (English Department FBS UNP, 2022)
Learning activities from home impacts changing students' lifestyles, especially reading activities. This study aimed to describe and explain reading interest among undergraduate students of the Indonesian Language and Literature Education Study Program (S-1 PBSI) of Universitas Sebelas Maret (UNS) while learning from home during the COVID-19 pandemic. This study was qualitative research with a descriptive survey method. The sampling technique was designed for S-1 PBSI UNS who are still active in the Academic Year 2021/2022. The data collection technique in this study employed a questionnaire consisting of five categories:1) attitudes toward reading, 2) reading preferences, 3) reading frequency, 4) reading sources, and 5) types of reading materials during learning from home. The following conclusions are reached as the research results and discussion. First, students still had an enthusiastic attitude towards reading activities while learning from home and reading anything, including books or academic material. Second, students preferred to read online with the fiction reading type in the form of novels rather than literary texts. Third, students' reading frequencies during learning from home were 30 minutes to 1 hour for 3–6 days a week. Students could read for more than one hour for fun, but only 30 minutes to 1 hour to read academic texts. Additionally, they could read 4–6 books in one semester. Fourth, students received online learning resources, mostly websites, and offline learning sources, primarily textbooks. Smartphones were the most commonly used reading media. Fifth, the majority types of student reading were novels.